Tet-mediated covalent labelling of 5-methylcytosine for its genome-wide detection and sequencing - Zhang, Liang (2013)
5-methylcytosine is an epigenetic mark that affects a broad range of biological functions in mammals. The chemically inert methyl group prevents direct labelling for subsequent affinity purification and detection. Therefore, most current approaches for the analysis of 5- methylcytosine still have limitations of being either density-biased, lacking in robustness and consistency, or incapable of analysing 5-methylcytosine specifically. Here we present an approach, TAmC-Seq, which selectively tags 5-methylcytosine with an azide functionality that can be further labelled with a biotin for affinity purification, detection and genome-wide mapping. Using this covalent labelling approach, we demonstrate high sensitivity and specificity for known methylated loci, as well as increased CpG dinucleotide coverage at lower sequencing depth as compared with antibody-based enrichment, providing an improved efficiency in the 5-methylcytosine enrichment and genome-wide profiling.